The Role of Self-monitoring and Self-efficacy on the Athletes’ Motivation and Performance: Evidence from Athlete Training Institutions in Indonesia - Setiyo Hartoto; Awang Firmansyah; Bayu Budi Prakoso; Novadri Ayubi; Satwika Arya Pratama; Abi (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Self-efficacy and self-monitoring are crucial for achieving an athlete's motivation and performance, which is the most important factor for the team's success. This feature deserves the attention of researchers, and the current work explores the effect of self-efficacy and self-monitoring on the performance of athletes in Indonesian training institutes. The study also investigates the mediating effect of self-monitoring between self-efficacy, self-monitoring, and athlete performance in Indonesian athletic training institutes. The study also utilized the primary data collected via survey questionnaires from the athletes. The study also employed smart PLS to examine the relationship between the understudy constructs. Self-efficacy and self-monitoring were found to have a good relationship with athletes' performance in Indonesian training institutes. The results also demonstrated that athlete motivation strongly influences the relationship between self-efficacy, self-monitoring, and athlete performance in Indonesian athletic training institutes. This research focuses on using self-efficacy and self-monitoring to enhance an athlete's performance, which guides policymakers.